On trusting ethnography: serendipity and the reflexive return to the fields of Gujarat. (30th August 2017) - Tilche, Alice; Simpson, Edward
Abstract: We draw on David Pocock's fieldwork of the 1950s in central Gujarat, India, as a comparative resource to think about social change and anthropological knowledge. Revisiting where Pocock had been through new fieldwork, we were encouraged to think about the ways in which places are accessed and subsequently understood. Against our conscious will, the pathways we were able to take through the field strongly resembled those Pocock took sixty years earlier. The coincidence is such that the material casts shadows of doubt over the potency of terms such as 'serendipity' and 'chance' to characterize key moments of ethnographic fieldwork. Against the primacy given to the self in much reflexive anthropology, we demonstrate that the personal attributes of the anthropologist might influence the production of ethnographic research less than is generally assumed. The double bind of our 'reflexive return' comes from revisiting an anthropological field and experiencing the agency of that field in making what we can know.